2018
DOI: 10.1002/adma.201802329
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Photoinduced Electron Transfer in a Zr‐MOF: Toward Solid‐State Fluorescent Molecular Switch and Turn‐On Sensor

Abstract: The immobilization of fluorescent photoinduced electron transfer (PET) switches/sensors into solid state, which usually cannot maintain their identical properties in solution, has remained a big challenge. Herein, a water-stable anthracene and maleimide appended zirconium-based-metal-organic framework (Zr-MOF; UiO-68-An/Ma) is reported. Unlike the regular intramolecular "fluorophore-spacer-receptor" format, the separated immobilization of fluorescent (anthracene) and acceptor (maleimide) groups into the framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 59 publications
0
73
0
Order By: Relevance
“…It was found that the fluorescence properties of UiO‐68‐An/Ma can be tuned in solid‐state by adjusting the scale of electron acceptance of the maleimide groups by Diels–Alder reaction or thiol‐ene reaction (Figure ). Moreover, UiO‐68‐An/Ma was also able to give a “naked eye” response at low biothiol concentration of 50 μmol L −1 within just 5 min . Recently, Ghosh and co‐workers reported a strategy for highly selective sensing of biothiols like cysteine by incorporating dinitrobenzenesulfonyl group through post‐synthetic modification (PSM) into a chemically stable MOF, UiO‐66‐NH 2 .…”
Section: “Turn On” Sensing Based On Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the fluorescence properties of UiO‐68‐An/Ma can be tuned in solid‐state by adjusting the scale of electron acceptance of the maleimide groups by Diels–Alder reaction or thiol‐ene reaction (Figure ). Moreover, UiO‐68‐An/Ma was also able to give a “naked eye” response at low biothiol concentration of 50 μmol L −1 within just 5 min . Recently, Ghosh and co‐workers reported a strategy for highly selective sensing of biothiols like cysteine by incorporating dinitrobenzenesulfonyl group through post‐synthetic modification (PSM) into a chemically stable MOF, UiO‐66‐NH 2 .…”
Section: “Turn On” Sensing Based On Mofsmentioning
confidence: 99%
“…Moreover,U iO-68-An/Ma was also able to give a" naked eye" response at low biothiol concentration of 50 mmol L À1 within just 5min. [55] Recently,G hosh and co-workers reported as trategy forh ighly selective sensing of biothiols like cysteine by incorporating dinitrobenzenesulfonyl group through post-synthetic modification (PSM) into a chemically stable MOF,U iO-66-NH 2 .T he highly reactive dinitrobenzenesulfonyl group reacts with the thiol functionalities present in cysteine resulting in high selectivity towards cysteine over other amino acids( Figure 13). [7]…”
Section: Sensing Of Bio-markersa Nd Biologically Active Compoundsmentioning
confidence: 99%
“…In addition, their linking efficiency with 8‐oxo‐dG is usually insufficient because of the small size of the target, [4d] limiting their detecting performances, especially in low concentrations; 3) most of the antibody‐/aptamer‐based probes require a long equilibrium period under specific conditions (pH, temperature, and ionic strength), which is a major concern during rapid and real‐time monitoring. More importantly, most previous luminescent sensors for biomolecules are primarily based on a single‐sensing mechanism or a single‐monitoring mode, which is insufficient for the reliable and precise quantification of the targets and easily causes false‐positive/negative diagnostic results. Increase of signal‐output/sensing channels will be favorable for the improvement of detection reliability .…”
Section: Introductionmentioning
confidence: 99%
“…[2,[18][19][20] However,amaterial exhibiting ESIPT properties in the solid or dispersives tate has potential to overcome these limitations. [32,33] In addition, flexible MOFs responsive to externals timuli [34,35] may be utilizedt of abricate excellentd evices relatedt os ensing, [4,36] data storage, [37] and molecular switches, [38] although some rigid MOFs, with or without ESIPT behavior,h ave also been found to be very suitable for sensing applications. [4] MOFs, as ac lass of crystalline microporous materials, are already highly celebrated due to their structure-property relationships, [21,22] which enables versatile applicationsi naw ide rangeo ff ields, including gas adsorption/storage, [23,24] electrical devices, [25,26] catalysis, [27][28][29] ion exchange, [30,31] and magnetic materials.…”
Section: Introductionmentioning
confidence: 99%
“…[4] MOFs, as ac lass of crystalline microporous materials, are already highly celebrated due to their structure-property relationships, [21,22] which enables versatile applicationsi naw ide rangeo ff ields, including gas adsorption/storage, [23,24] electrical devices, [25,26] catalysis, [27][28][29] ion exchange, [30,31] and magnetic materials. [32,33] In addition, flexible MOFs responsive to externals timuli [34,35] may be utilizedt of abricate excellentd evices relatedt os ensing, [4,36] data storage, [37] and molecular switches, [38] although some rigid MOFs, with or without ESIPT behavior,h ave also been found to be very suitable for sensing applications. [39][40][41] On the other hand, flexible MOFs showing structural dynamism can show unique selective, stepwise gas/vapor sorptionp rofiles that may facilitatet he separation as well as sensing of small molecules in the gas/vapor phase.…”
Section: Introductionmentioning
confidence: 99%